City of ashes - Clare, Cassandra (New York : Simon Pulse, 2009)
Sixteen-year-old Clary continues trying to make sense of the swiftly changing events and relationships in her life as she becomes further involved with the Shadowhunters and their pursuit of demons and discovers some terrifying truths about her parents, her brother Jace, and her boyfriend Simon.
Young Adult
Young Adult
School Library Journal
Horn Book
Bulletin (Center for Children's books)
HL 720
Keywords: Supernatural -- Juvenile fiction; Demonology -- Juvenile fiction; Magic -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Supernatural -- Fiction; Demonology -- Fiction; Magic -- Fiction; New York (N.Y.) -- Fiction; Supernatural -- Fiction; Demonology -- Fiction; Magic -- Fiction; New York (N.Y.) -- Fiction